M&E Systems and the Budget - Krause, Philipp (World Bank, Washington, DC, 2012)
Monitoring and evaluation (M&E) are means to multiple ends. Measuring government activities, constructing and tracking performance indicators across sectors and over time, evaluating programs, these activities can be carried out and tied together with different objectives in mind. It will certainly be possible to use M&E purely as a way to improve transparency and accountability, by making more information on the workings and results of government programs available to the public. One can also focus M&E on managerial purposes, to reward performance inside ministries and agencies. But surely a crucial element of running an effective public sector will be missing if M&E were not used to inform the spending of public money. This briefing note will introduce the main issues surrounding M&E as a tool for budgeting, a system usually referred to as performance budgeting, to help policy makers make strategic decisions about their M&E systems by outlining different design choices and their respective advantages and pitfalls.